How will regional brewers and their cask beer brands survive and prosper in the face of market changes resulting from Government intervention? - Jespersen, Paul (2007)
This project is a study of the current state of the cask beer market in England, focussing on one particular regional cask beer producer, "A". The project has been undertaken with two main objectives in mind.